2018
DOI: 10.1016/j.dadm.2018.10.003
|View full text |Cite
|
Sign up to set email alerts
|

CSF total tau levels are associated with hippocampal novelty irrespective of hippocampal volume

Abstract: Introduction We examined the association between cerebrospinal fluid (CSF) biomarkers of Alzheimer's disease, neural novelty responses, and brain volume in predementia old age. Methods We conducted a cross-sectional analysis of the observational, multicentric DZNE-Longitudinal Cognitive Impairment and Dementia Study (DELCODE) study. Seventy-six participants completed task functional magnetic resonance imaging and provided CSF (40 cognitively unimpaired, 21 experiencing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
83
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

6
1

Authors

Journals

citations
Cited by 42 publications
(87 citation statements)
references
References 43 publications
4
83
0
Order By: Relevance
“…In future work, investigating the neural fate of memorable and forgettable images in older individuals and those with SCD or MCI may aid in understanding how patients may differentially process images at different processing stages of perception and memory encoding. In the DELCODE study, we have indeed obtained fMRI data alongside the behavioral data reported here [15] and will be able to address this question in the future. A related question is how Alzheimer's pathology is related to memorability.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…In future work, investigating the neural fate of memorable and forgettable images in older individuals and those with SCD or MCI may aid in understanding how patients may differentially process images at different processing stages of perception and memory encoding. In the DELCODE study, we have indeed obtained fMRI data alongside the behavioral data reported here [15] and will be able to address this question in the future. A related question is how Alzheimer's pathology is related to memorability.…”
Section: Discussionmentioning
confidence: 90%
“…A related question is how Alzheimer's pathology is related to memorability. For instance, we have previously shown that increasing levels of CSF total tau are related to decreasing novelty responses in the amygdala and the hippocampus [15]. These functional consequences of tau pathology could influence memorability patterns in MCI or SCD.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In future work, investigating the neural fate of memorable and forgettable images in older individuals and those with SCD or MCI may aid in understanding how patients may differentially process images at different processing stages of perception and memory encoding. In the DELCODE study, we have indeed obtained fMRI data alongside the behavioral data reported here [11] and will be able to address this question in the future. A related question is how Alzheimer’s pathology is related to memorability.…”
Section: Discussionmentioning
confidence: 99%
“…Visual memory tests were analyzed from the DZNE-Longitudinal Cognitive Impairment and Dementia Study (DELCODE), an observational, longitudinal memory clinic-based study across 10 sites in Germany. Specific details about this study, the visual memory task, and data handling and quality control are reported in Jessen et al [10] and Düzel et al [11]. The data analyzed in this study were from the second data release from the DELCODE study comprising of 700 individuals of which 394 participants with complete datasets were analyzed, including 136 participants with SCD, 65 with MCI, and 193 HC.…”
Section: Methodsmentioning
confidence: 99%